Enhancing antimicrobial management: A 5-year retrospective analysis of urinary pathogen susceptibility at a tertiary care centre from January 2018 to December 2022 - Ashish William; Deepti Rawat; Shweta Satija; Ravinder Kaur (​​​One Health Bulletin)
Objective: The study aims to collect data on prevalence and antibiotic susceptibility patterns of uropathogens in a hospital in India, and to analyze any changes that have occurred over the past 5 years. Methods: This retrospective study was conducted over 5 years at Lady Hardinge Medical College & Associated Hospitals, New Delhi. Urine samples from patients who attended outpatient department or were admitted with diagnosis of urinary tract infection (UTI) were included in this study. Samples were cultured and tested to identify bacteria and determine antibiotic susceptibility using the Kirby-Bauer disc diffusion method. Results: A total of number of 151 395 urine specimens were collected from January 2018 to December 2022. The prevalence of UTI was 7.5% (11 372/151 395) with the majority of patients being aged above 40 years (19.3%). The prevalence was higher in females (12.7%) as compared to males (3.2%). Escherichia coli was the predominant pathogen, accounting for 59.8% of cases, followed by Klebsiella spp. at 18.9%, and Enterococcus spp. at 8.3%. Gram-negative bacteria accounted for 89.5% of the isolates and exhibited good susceptibility to aminoglycosides and piperacillin-tazobactam, but showed resistance to fluoroquinolones. Methicillin-resistant Staphylococcus aureus (MRSA) was present in 35% of Staphylococcus aureus isolates with high susceptibility to glycopeptides and nitrofurantoin. Conclusions: The data suggest the need for careful selection of empirical therapy due to increasing resistance patterns. The stringent use of antimicrobial agents is pivotal to the control of antimicrobial resistance. Antibiotic susceptibility data contributes to tailoring the antibiotic stewardship programs to local needs.